"Emblems of Adversity": W.B. Yeats's Poetics of Violence and Contemporary Northern Irish Poetry - Sperry, Amanda (Wake Forest University, 2009)
W. B. Yeats’s poetry presents an interconnected world where desire is the progenitor of both violence and artistic expression. His poetry explores the interaction of art and violence. Poets from the North of Ireland such as Seamus Heaney and Nick Laird represent the dual legacy of W. B. Yeats’s poetics in a society where violence has been the norm. Yeats’s legacy influences both Heaney’s poetry that attempts to mitigate violence with art, and Laird’s poetry that attempts to expose violence with art. Reading W. B. Yeats’s poetry through the lens of the poets that follow him allows an exploration of alternative strategies for viewing and reacting to violence.
Keywords: Literature; Irish poetry; Yeats, W. B.; Heaney, Seamus